The Influence of Financial Literacy on Welfare through Financial Inclusion - Asep, Asep (Dinasti Publisher, 2024)
This study aims to analyze the impact of Islamic financial literacy on individual welfare by considering the role of Islamic financial inclusion, Financial inclusion can produce maturity of response to financial situations, so that it focuses on financial decision-making planning. The low Islamic financial literacy index is an indicator of the suboptimal use of Islamic financing, which then the achievement of welfare has not been achieved, this study uses a quantitative approach with a survey method on a group of respondents in Karawang Regency, West Java. The results of the study indicate that high Islamic financial literacy contributes positively to Islamic financial inclusion, which ultimately improves individual financial welfare. The path coefficient (mediation) shows that the indirect effect of Islamic financial literacy on social welfare through Islamic finance is 0.190, and the Z-score (Sobel test) is (6.661) which is greater than 1.96, and the conclusion is that Islamic financial literacy has a positive impact on welfare through Islamic financial inclusion. These findings highlight the importance of education and increasing Islamic financial literacy to improve welfare through access to financial services in accordance with Islamic principles